Pragmatism, ideology or politics? : Trade unions and workers' responses to the imposition of neo-liberalism in Argentina (1976-2010) - Atzeni, Maurizio (2011)
Since 1976, responding to macroeconomic international variables, local political struggles and social conflicts, different phases of neo-liberal inspired market reforms have been implemented in Argentina. Four main phases can be identified, each corresponding to a specific economic–political context. The imposed consensus of the military dictatorship of the period 1976-1983, the structural and fiscal adjustments of the return to democracy in 1983-1989, the massive neoliberal program of privatizations, reform of the public sector, labour flexibility and attack on workers’ rights implemented during the 1990s but opened by the economic terror of the hyperinflation of 1989-1990, the neo-developmental and agricultural commodities export oriented model of the post 2001 crisis.